2003
DOI: 10.1038/nature01889
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lps2 as a key transducer of MyD88-independent TIR signalling

Abstract: In humans, ten Toll-like receptor (TLR) paralogues sense molecular components of microbes, initiating the production of cytokine mediators that create the inflammatory response. Using N-ethyl-N-nitrosourea, we induced a germline mutation called Lps2, which abolishes cytokine responses to double-stranded RNA and severely impairs responses to the endotoxin lipopolysaccharide (LPS), indicating that TLR3 and TLR4 might share a specific, proximal transducer. Here we identify the Lps2 mutation: a distal frameshift e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
954
6
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,121 publications
(999 citation statements)
references
References 31 publications
37
954
6
2
Order By: Relevance
“…Subsequent studies identified TIR domain-containing adaptor-inducing IFN-b (TRIF), also known as TIR-containing adaptor molecule (TICAM)-1, as the key regulator of the Myd88-independent pathway. TRIF-knockout mice, or mice with a frame shift mutation resulting in a truncated form of TRIF, fail to show Myd88-independent activation of NF-kB and are non-responsive to LPS or the TLR3 ligand poly(I:C), with respect to the expression of IFN-inducible genes [20,21]. TRIF interacts directly with the TIR domain of TLR3 [22] and mediates signalling, whereas another TIR domaincontaining adaptor TRIF-related adaptor molecule (TRAM), also known as TICAM-2, acts as a bridging adaptor between TLR4 and TRIF [23].…”
Section: Myd88-dependent Signalling and Activation Of Nf-kbmentioning
confidence: 99%
“…Subsequent studies identified TIR domain-containing adaptor-inducing IFN-b (TRIF), also known as TIR-containing adaptor molecule (TICAM)-1, as the key regulator of the Myd88-independent pathway. TRIF-knockout mice, or mice with a frame shift mutation resulting in a truncated form of TRIF, fail to show Myd88-independent activation of NF-kB and are non-responsive to LPS or the TLR3 ligand poly(I:C), with respect to the expression of IFN-inducible genes [20,21]. TRIF interacts directly with the TIR domain of TLR3 [22] and mediates signalling, whereas another TIR domaincontaining adaptor TRIF-related adaptor molecule (TRAM), also known as TICAM-2, acts as a bridging adaptor between TLR4 and TRIF [23].…”
Section: Myd88-dependent Signalling and Activation Of Nf-kbmentioning
confidence: 99%
“…Lps2, a non-functional codominant allele of Trif, was induced by N-ethyl-N-nitrosourea mutagenesis on a pure C57BL/6 mouse background [49] in the Scripps Institute animal facilities (La Jolla CA). C3H/HeN, C3H/HeJ, C57BL/10ScN, C57BL/10ScSn, C57BL/6, Trif Lps2/ Lps2 , Trif Lps2/WT , C57BL/6 Myd88 -/-, C57BL/6 Tlr4 -/-and C57BL/6/129 Trif -/-mice were bred at the MIG animal facilities (Lund, Sweden).…”
Section: Mouse Strainsmentioning
confidence: 99%
“…IRF-3 and expression of IFN-g [17,18]. Moreover, production of certain inflammatory cytokines in response to LPS and poly(I:C) but not upon stimulation of TLR2, TLR7, and TLR9 was severely impaired in TRIF-defective macrophages and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the adaptor protein TRAM interacts with TRIF and is required for MyD88-indpendent signaling of TLR4 but not TLR3 [19,20]. Combined null mutations for both TRIF and MyD88 completely abrogated signal transduction by TLR4, suggesting that only these two signaling pathways emanate from TLR4 [17,18].…”
Section: Introductionmentioning
confidence: 99%